Fundamentals of nursing - Potter, Patricia A.; Perry, Anne Griffin (St. Louis, Missouri : Mosby Elsevier, 2001)
This textbook is designed for beginning students in all types of professional nursing programs. The compreensive coverage provides fundamental nursing concepts, skills, and techniques of nursing programs.
Unit 1. The Client and the Health Care Environment. 1. Health and Wellness. 2. The Health Care Delivery System. 3. Community-Based Nursing Practice. 4. Leadership, Delegation, and Quality Management. 5. Theoretical Foundations of Nursing Practice -- Unit 2. Caring Throughout the Life Span. 6. Nursing Healing and Caring. 7. Diversity in Caring. 8. Caring in Families. 9. Developmental Theories. 10. Conception Through Adolescence. 11. Young to Middle Adult. 12. Older Adult -- Unit 3. Critical Thinking in Nursing Practice. 13. Critical Thinking and Nursing Judgment. 14. Nursing Assessment. 15. Nursing Diagnosis. 16. Planning for Nursing Care. 17. Implementing Nursing Care. 18. Evaluation -- Unit 4. Professional Standards in Nursing Practice. 19. Professional Nursing Roles. 20. Ethics and Values. 21. Legal Implications in Nursing Practice. 22. Communication. 23. Client Education. 24. Documentation. 25. Research as a Basis for Practice -- Unit 5. Psychosocial Basis for Nursing Practice. 26. Self-Concept. 27. Sexuality. 28. Spiritual Health. 29. Responding to Loss, Death, and Grieving. 30. Stress and Adaptation -- Unit 6. Scientific Basis for Nursing Practice. 31. Vital Signs. 32. Health Assessment and Physical Examination. 33. Infection Control. 34. Medication Administration. 35. Complementary and Alternative Therapies -- Unit 7. Basic Human Needs. 36. Activity and Exercise. 37. Safety. 38. Hygiene. 39. Oxygenation. 40. Fluid, Electrolyte, and Acid-Base Balances. 41. Sleep. 42. Comfort. 43. Nutrition. 44. Urinary Elimination. 45. Bowel Elimination -- Unit 8. Clients With Special Needs. 46. Mobility and Immobility. 47. Skin Integrity and Wound Care. 48. Sensory Alterations. 49. Surgical Client.
Includes bibliographical references.
Keywords: NURSING CARE